Preliminary Thermodynamic Analysis of Magnetohydrodynamic Generators in Combined Cycles for Enhanced Energy Efficiency - Huda Ali Hussein (Academia Open, 2025)
General Background: Magnetohydrodynamic (MHD) generators offer direct thermal-to-electric conversion and have long been explored as a method to surpass the efficiency limits of conventional combined cycle systems. Specific Background: Integrating an open-cycle MHD generator as a topping cycle within a gas–steam combined cycle has been proposed to exploit ultra-high combustion temperatures and enhance overall plant efficiency. Knowledge Gap: Despite previous experimental programs, comprehensive thermodynamic evaluations of MHD performance within modern combined cycles—considering updated plasma conductivity models, material improvements, and carbon-capture compatibility—remain limited. Aims: This study analyzes the thermodynamic behavior of an open-cycle MHD generator fueled by coal-derived syngas or natural gas and evaluates its efficiency contribution when integrated into a combined cycle. Results: Quasi-one-dimensional simulations show MHD enthalpy extraction near 22%, subsystem isentropic efficiency of 28%, and overall cycle efficiencies of 56–60%, outperforming conventional CCGT systems by 10–15%. Novelty: The study integrates validated MHD flow modeling with modern combined-cycle configurations, incorporating updated material solutions and non-equilibrium ionization strategies. Implications: Findings highlight MHD-combined cycles as a promising pathway for high-efficiency, low-carbon power generation and provide guidance for future pilot-scale implementation and carbon-capture-ready system design.Highlight : The study emphasizes efficiency gains of 56–60 percent achieved through integrating MHD generators into combined cycles. It highlights how magnetic field strength, high-temperature plasma, and conductivity improvements drive overall performance. The content also identifies key challenges, including electrode erosion and material durability, and discusses proposed technical solutions. Keywords : Magnetohydrodynamic Generator, Combined Cycle, Thermodynamic Efficiency, Plasma Conductivity, Energy Conversion